The business ethics activity book : 50 exercises for promoting integrity at work - Caroselli, Marlene (AMACOM, 2003)
Annotation Companies in every industry are recommitting themselves to creating environments of honesty and renewing trust with their customers, employees, and the general public. But it's not as easy as it sounds. Even in "good" organizations, proactive ethics initiatives are still a very new concept, and the question remains, "How do we do this?" The answer can be found in the 50 exercises in The Business Ethics Activity Book. These ready-to-use, easily adaptable activities will engage individuals, teams, and groups and generate the kind of thought and discussion that ultimately leads to mutual respect and an atmosphere in which ethical behavior defines organizational culture. Book jacket
Keywords: Business ethics.; Leadership -- Moral and ethical aspects.; elektronické knihy; electronic books